Simulation model of 3-phase PWM rectifier by using MATLAB/Simulink - Salam Waley Shneen; Ghada Adel Aziz (Institute of Advanced Engineering and Science, 2021)
Many industrial applications require the use of power electronic devices, which in turn help in overcoming the problems of variable load and fluctuations that occur at the end of feeding. The current study emphasizes that the use of different electric power generation systems with industrial applications needs control devices to work on improving the power quality and performance of systems in which there is an imbalance in the voltage or current due to the change of loads or feeding from the source. The present study also presents a model of a transformer widely used in industrial applications and this work includes simulating a three-phase rectifier by MATLAB. There are four cases in this work HWR (uncontrolled and controlled) and FWR (uncontrolled and uncontrolled) with different loads (R, RL & RC) including full wave type AC/DC using six electronic transformer silicon control rectifier (SCRs) once as well as unified half wave using three electronic transformer silicon control rectifier (SCRs). Simulation results include input, output voltage, and current with the waveform.